IMPLEMENTASI SISTEM PEMBAYARAN DIGITAL QRIS DALAM MENINGKATKAN PENJUALAN UMKN FC SARJANA - Misbahul Aulia; Erwinsyah; Phatra Anggana Djuri; Femilia Zahra (Jurnal Nusa Manajemen, 2025)
This study examines the implementation of the Quick Response Code Indonesian Standard (QRIS) digital payment system in a student-run photocopy business, FC Sarjana. The research aims to analyze how the adoption of QRIS influences transaction efficiency, financial recording, and potential sales growth. A qualitative descriptive approach was employed, utilizing field observations and in-depth interviews with the owner, employees, and customers. The findings reveal that QRIS facilitates smoother transactions, particularly for students who rarely carry cash, and supports automatic financial recording. Moreover, QRIS enhances the image of the business as modern and professional. However, challenges remain in terms of customer trust in digital proof of payment and dependence on internet connectivity. This study contributes theoretically by expanding the discussion on financial technology adoption in micro-service sectors and offers practical recommendations for micro, small, and medium enterprises (MSMEs) in leveraging QRIS to strengthen their competitiveness.